Financialization, banking concentration and financial inclusion: the reproduction of structural heterogeneity in the financial complexes of Argentina and Mexico - Giovanni Villavicencio (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This paper analyzes the behavior and dynamics of the banking sector in underdeveloped economies in times of financialization, using the cases of Argentina and Mexico. We argue that financialization has increased banking concentration and the participation of too big to fail financial institutions in the banking sector of underdeveloped countries. We argue that the banking predominance has not been reflected in an increase in financial inclusion, but has exacerbated social inequalities, reconfiguring what is understood as underdeveloped in the 21st century